Relationship between Covid-19 pandemic and firm’s performance towards unemployment across countries - Saad , Noriza Mohd (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As a result of the consequences of the Covid-19 pandemic, stock market players issued their quick response on how coronavirus has affected the performance of firms whereby most of the affected sectors are airlines, tourism, hotels, transportation and many more. This has led to an increase in the unemployment rate worldwide. Considering this global issue, this study was aimed at investigating the relationship between unemployment with a number of confirmed cases of Covid-19 and firms’ performance as well as the controlling factors across seven (7) countries. Secondary data were utilized with the data obtained from Bloomberg and Worldometers website. The dataset for dependent as proxy by unemployment rate and explanatory variables proxies by COVID-19 and firm’s performance were then tested using multivariate regression approach. Finally, from the study, it is suggested that an increase in the number of Covid-19 cases will affect business performance as controlled by macroeconomics factors which lead to a significant positive relationship between the unemployment rates in all the countries of this study. This factor may affect the government’s decision to implement the Movement Control Order (MCO), for instance by the Malaysian Government. By Covid-19 vaccine development in the market nowadays, hopefully, the spread can be mitigated and firms’ performance can return to normalcy to avoid increasing rate of unemployment in the world.